2001
DOI: 10.1046/j.1440-1711.2001.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolactin is associated with apoptosis in men with human immunodeficiency virus infection

Abstract: SummaryWe examined the in vivo and in vitro production of prolactin (PRL) in 20 untreated HIV-infected men compared to 14 uninfected men and its association with the cell cycle and apoptosis. Compared to uninfected men, the HIV-infected men had: (i) higher fasting serum bioactive (BIO) PRL; (ii) lower serum immunoreactive (RIA) and BIO-PRL responses to intravenous metoclopramide; (iii) greater BIO-RIA PRL ratio both fasting and during intravenous metoclopramide; (iv) lower percentage of non-stimulated PBMC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In this regard, our findings may have clinical relevance because PRL has pleiotropic effects and limited toxicity after systemic administration in animals 47 . Therefore, the possibility of using recombinant human PRL as an adjunct therapeutic approach to favour immune reconstitution in HIV‐infected patients does not seem inappropriate 18 , 20 , 47 , 48 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In this regard, our findings may have clinical relevance because PRL has pleiotropic effects and limited toxicity after systemic administration in animals 47 . Therefore, the possibility of using recombinant human PRL as an adjunct therapeutic approach to favour immune reconstitution in HIV‐infected patients does not seem inappropriate 18 , 20 , 47 , 48 .…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies using the intravenous administration of metoclopramide, have indirectly suggested the existence of low DA tone in HIV‐infected men (an abnormality which cannot be detected by measuring serum PRL in a single blood specimen) in an effort to maintain the highest physiologic PRL release and to stimulate lymphocyte proliferation at a maximal possible rate 16 , 17 . This might represent an adaptive mechanism in an attempt to survive which also could even have therapeutic implications 18 , 19 , 20 . Furthermore, the effect of highly active antiretroviral therapy (HAART) on endocrine status in HIV‐infected subjects has not been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the range of serum prolactin levels is much higher in female than in male, and thus the differences based on the responses to infection would not be discriminated in female subjects. Thus the prolactin studies of many infectious diseases [Croxson et al, ; Graef et al, ; Montero et al, ; Parra et al, ; Collazos et al, ; Leanos‐Miranda and Contreras‐Hernandez, ] had been selected for the male subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the range of serum prolactin levels is much higher in female than in male, and thus the differences based on the responses to infection would not be discriminated in female subjects. Thus the prolactin studies of many infectious diseases [Croxson et al, 1989;Graef et al, 1994;Montero et al, 2001;Parra et al, 2001;Collazos et al, 2002;Leanos-Miranda and Contreras-Hernandez, 2002] had been selected for the male subjects. Recently, some studies showed that hyperprolactinemia was found in patients with chronic hepatitis C as a part of abnormality of hormone parameters [Durazzo et al, 2006;Hofny et al, 2011] or with an association of hyperferritinemia [Sousa et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation